Sistem Informasi Perhotelan Front Office Menggunakan Metode OOAD untuk Meningkatkan Pelayanan Customer: Studi Kasus Perhotelan-Open Source - Christian, Lianawati; Permatasari, Angelina; Sugandi, Lianna (Bina Nusantara University, 2013)
Technology plays an important role in various enterprise business processes for improved customer service, decision making, and means of information exchange. Hospitality accommodation is an example of fields that use information systems technology. This research was conducted in the field of hospitality especially front office system. Using computerized front office system, data about guests will be stored more safely and the reports will be better resulted. The purpose of this study is to analyze the existing problems on a Front Office of a hotel including identifying information needs and designing information systems to improve hospitality services to guests. The method used is analysis and design. Analysis is performed towards library research anddata collection needed for measuring through observation, interviews, and documents related to the information system. Menawhile, design uses object oriented analysis and design (OOAD) method and application programusing MS Access 2010. The result achieved is an application design of information system of hospitality front office that consists of five modules, namely Reservation module, Services module, Housekeeping module,Restaurant module, and Billing module. As a conclusion, a computerized information system of hospitality front office can assist hotels in providing better service to guests, which in turn can increase guest satisfaction.